Electron-Microscopic Studies on the Palatine Tonsil of the Buffalo (Bubalus bubalis) - Girgiri, Ibrahim Alhaji; Kumar, Pawan (Journal of Buffalo Science, 2021)
The study examined the ultrastructural features of the palatine tonsils of the local mixed breed of adult buffaloes using scanning and transmission electron microscopy. The tissue samples collected from the palatine tonsils were fixed in 2% glutaraldehyde solution and processed for scanning and transmission electron microscopy. The scanning electron microscopy of the tonsil's surface epithelium presented folded mucosa consisting of folds divided by shallow grooves. The mucosal surface was having a squamous arrangement of cells that were delineated from the adjacent cells. These cells at higher magnification presented the microplicae, which appeared as if filled with material. A few small duct openings were irregularly placed throughout the mucosal surface. The transmission electron-microscopy elaborated structural details of the distinct strata of the surface and reticular epithelia, the cell organelles as well as the lymphocytes migration across the high endothelial venules. The vesiculo-vacuolar organelle was also observed. The study provided detailed ultramicroscopic features of the palatine tonsil, which might play a significant role in the induction of immunity against ingested antigens sampled at the mucosal surface.